Effects of media messages on disordered eating development among female collegiate distance runners - Perrin, Megan-Anne (Kansas State University, 2012)
This study was an examination of the determinants of disordered eating development among female collegiate distance runners. More specifically, the study examined the impact of thinness-emphasizing and thinness-promoting messages disseminated by mass media and running-specific media, and how those messages affected disordered eating among a sample of female collegiate distance runners. It also examines current female collegiate distance runners’ attitudes toward disordered eating, subjective norms from referent individuals close to female collegiate distance runners regarding disordered eating, and female collegiate distance runners’ perceived behavioral control regarding disordered eating—which was divided into various internal and external control factors either inhibiting or facilitating disordered eating among them. The study was qualitative in nature and assumed a multi-method approach. It included an online, anonymous, self-administered questionnaire among 166 current NCAA Division I female distance runners; four small, confidential focus groups with current NCAA Division I female distance runners from four different teams; and 16 in-depth interviews with professional distance runners, dietitians, coaches, physicians, and sports psychologists. The study sought to answer four research questions—each based on an element of the study’s guiding theory, the theory of planned behavior (Ajzen, 1991). Overall, the study found media messages, attitudes, subjective norms, and various internal and external control factors all facilitated disordered eating among NCAA Division I female distance runners. Based upon these findings, the study offers recommendations for practitioners in the field of health communication, coaches, academic institutions with cross country and track teams, and female collegiate distance runners.
Keywords: Disordered eating; Eating disorder; Runner; Theory of planned behavior; Media effects; Media; Mass Communications (0708); Medicine (0564); Nutrition (0570)